2006
DOI: 10.1146/annurev.astro.44.051905.092532
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Properties of Black-Hole Binaries

Abstract: We review the properties and behavior of 20 X-ray binaries that contain a dynamically-confirmed black hole, 17 of which are transient systems. During the past decade, many of these transient sources were observed daily throughout the course of their typically year-long outburst cycles using the large-area timing detector aboard the Rossi X-ray Timing Explorer. The evolution of these transient sources is complex. Nevertheless, there are behavior patterns common to all of them as we show in a comprehensive compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

106
2,268
4
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,316 publications
(2,395 citation statements)
references
References 174 publications
(199 reference statements)
106
2,268
4
17
Order By: Relevance
“…These observations are very similar in flux (5 per cent difference using best-fit single component models), but have very different spectral shapes. The spectral states of BHBs (Remillard & McClintock 2006) and some ULXs have also been shown to be degenerate with luminosity, and Grisé et al (2010) showed similarly for the ULX Ho II X-1 that spectral transitions occurred without a significant change in luminosity. Based on high-energy spectral curvature, X-1 appears to be in a super-Eddington state in its highest luminosity observations, as has been suggested by previous authors (Watarai et al 2001;Ebisawa et al 2003;Feng & Kaaret 2009;Yoshida et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…These observations are very similar in flux (5 per cent difference using best-fit single component models), but have very different spectral shapes. The spectral states of BHBs (Remillard & McClintock 2006) and some ULXs have also been shown to be degenerate with luminosity, and Grisé et al (2010) showed similarly for the ULX Ho II X-1 that spectral transitions occurred without a significant change in luminosity. Based on high-energy spectral curvature, X-1 appears to be in a super-Eddington state in its highest luminosity observations, as has been suggested by previous authors (Watarai et al 2001;Ebisawa et al 2003;Feng & Kaaret 2009;Yoshida et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In this case, particle re-acceleration behind shocks further out in the jet launching region will be probably the main responsible for the radio emission. The violent MR could also be responsible for the transition from the so called hard steep power-law state (SPLS) to the soft SPLS in microquasars (Remillard & McClintock, 2006).…”
Section: Mr In Microquasars and Agnsmentioning
confidence: 99%
“…Observationally, galactic BH binaries show two spectral states, the low/hard state (hereafter LHS) which is dominated by a power-law spectrum, possibly corresponding to the RIAF, and the high/soft state (hereafter HSS) which is dominated by an optically-thick thermal emission from an accretion disk, i.e. the standard-disk (Tanaka & Shibazaki 1996;Remillard & McClintock 2006;Done et al 2007). In the HSS, a hard tail component is seen in the energy spectrum, which often extends from 10 keV to several MeV by a powerlaw (Gierliński et al 1999).…”
Section: Introductionmentioning
confidence: 99%